2009
DOI: 10.1186/1756-9966-28-79
|View full text |Cite
|
Sign up to set email alerts
|

Viscum album L. extracts in breast and gynaecological cancers: a systematic review of clinical and preclinical research

Abstract: Background: Viscum album L. extracts (VAE, European mistletoe) are a widely used medicinal plant extract in gynaecological and breast-cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
2
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(97 citation statements)
references
References 85 publications
5
85
2
5
Order By: Relevance
“…A survey on patients' perception of health status carried out on women with breast and gynecologic malignancies showed that CAM use (and MT corresponded to 77% of it) is associated with a better coping with the disease. 26 The statistically significant decrease in fatigue during MT detected in our study by the EORTC QLQ-C30 questionnaire supports results from previous studies that included breast cancer patients being treated with chemotherapy 5 and corroborates the higher vitality of the patients mentioned during the second interview. Furthermore, a decrease of cancer-related fatigue associated with MT was shown in a case report.…”
Section: Progression Of Qol During the 3 Months Of Mtsupporting
confidence: 89%
“…A survey on patients' perception of health status carried out on women with breast and gynecologic malignancies showed that CAM use (and MT corresponded to 77% of it) is associated with a better coping with the disease. 26 The statistically significant decrease in fatigue during MT detected in our study by the EORTC QLQ-C30 questionnaire supports results from previous studies that included breast cancer patients being treated with chemotherapy 5 and corroborates the higher vitality of the patients mentioned during the second interview. Furthermore, a decrease of cancer-related fatigue associated with MT was shown in a case report.…”
Section: Progression Of Qol During the 3 Months Of Mtsupporting
confidence: 89%
“…Darüber hinaus wurden 1693 diesbezüglich erfahrene Ärzte zur Sicherheit injizierbarer AM-Präparate befragt, nur selten waren Nebenwirkungen beobachtet worden [1,67]. Im Kontext der klinischen Studien wurde in der Regel das Auftreten von UAW erhoben [1,14,15]. Hier zeigten sich gelegentlich milde und selbstlimitierte UAW.…”
Section: Introductionunclassified
“…In a comparable retrospective study design in pancreatic cancer patients, similar clinical outcomes were observed with fewer adverse events and improved survival in patients treated with mistletoe [33]. Despite compelling preclinical data and these isolated reports of clinical benefit of mistletoe preparations, recent reviews of clinical trials still note methodological weaknesses of current published studies on mistletoe [34] as well as conflicting results on tumor response and survival prolongation on treatment using various mistletoe preparations [35][36][37][38]. A number of recently published studies confirm this mixed picture [39][40][41][42].…”
Section: Introductionmentioning
confidence: 86%